Chaim Weizmann. A biography by several hands. With a preface by D. Ben- Gurion. Ed. by M.W. Weisgal and J. Carmichael. [Contribs by I. Berlin, M. Samuel, I.M. Sieff a.o.] (Weidenfeld and Nicolson, 1962)
With ills, index and prt.